Evaluation of Cohesion Policy in Romania: New perspectives - Teodora Diana Iacob (CES Working Papers, 2017)
The 2014-2020 programming period has brought several changes in terms of programming the Cohesion Policy at European level. Based on the lessons learned from past experiences, the new vision for the implementation of interventions financed under the European Structural and Investment Funds determined the consolidation of some key instruments, including programme evaluation. Taking into consideration that Romania is presently evaluating its second generation EU financed programmes, the objective of the article is to analyse, in a comparative manner, the two planning phases of evaluation of Cohesion Policy in Romania. This will include the identification of the main changes that occurred in terms of elaboration and implementation of evaluation plans and a short description of the progress related to the development of the evaluation capacity of public policies at national level since new requirements and responsibilities were established with the scope of achieving more and better policy results.
Keywords: 330; Cohesion Policy; programmes; evaluation function; evaluation plan; results